The Effect Of Stem Problem-Based Learning On Achievement In Simple Machines, Interest In Learning Science And Self-Regulated Learning In Science Among Junior Secondary School Students In Nigeria - Davidson, Vincent Chukwujekwu (2018)
The objective of this study was to examine the effect of STEM PBL on the Basic Science achievement test, interest in learning science and self-regulated learning in science. Specifically, the study was to assess the effect of STEM PBL on two groups of learners. These are the low ability learners and high ability learners. The study also tried to determine whether the effect of STEM PBL on Basic Science achievement test, interest in learning science and self-regulated learning in science was higher on low ability learners or high ability learners or whether the effect is the same for both groups. The study used stratified random sampling to compose a class of low ability learners and another class of high ability learners. The study employed preexperimental research design. There were two groups of learners, a pretest, post-test and a delayed post-test for low ability learners and high ability learners. The study was conducted as an out-of-school experiment so there was no need for a control group. The treatment was lasted for three months. The independent variable is STEM PBL, there were three dependent variables are Basic Science achievement test, interest in learning science and self-regulated learning in science. Learners’ ability was the moderating variable. It was found that STEM PBL positively affects Basic Science achievement test, interest in learning science and self-regulated learning in science. The effect was more for low ability learners than high ability learners. The study showed that STEM PBL could be a very good approach that will enable low ability learners to perform better in Basic Science.